Technical services in the 21st century - Hines, Samantha Schmehl (Advances in library administration and organization, 2021)
While librarianship in general has had to respond to constant revolutionary change, technical services have faced much more immediate challenges, having nearly been completely reimagined in the 21st century. By showcasing the work of technical services, and the ground-breaking changes they have encountered, this edited collection provides readers with an opportunity to re-assess the opportunities and challenges for library administration, and to understand how libraries should be managed in the future. Including thirteen chapters from a variety of libraries, this collection examines several aspects of technical services work in the 21st century. The authors offer thoughtful applied theoretical solutions to practical problems encountered by library administrators and managers in four broad categories: planning and assessment, workflows, data, and acquisitions. Geared at library managers and administrators, readers of this volume may understand new trends in technical services work, how previous structures and workflows fit in and are evolving, and the new ways that in which we might describe, assess and carry out what we do in libraries.